Évaluation des facteurs de pénibilité du travail et évolutions technico-organisationnelles : un défi pour l’ergonomie - Annabelle Chassagnieux; Alain Garrigou; Monique Lortie; Catherine Teiger; Gabriel Carballeda; Vincent Pargade; Pierrick Pasquereau; Carole Perraut; Pascal Auguste; Philippe Escuredo; Gérard Kévorian (Perspectives Interdisciplinaires sur le Travail et la Santé)
Thirty years apart, ergonomists were asked the same question by trade unions and employer associations namely, to assess the occupational risks of rotary press operators and the impact on their health and life expectancy. This paper aims to present the method and main results of two studies led respectively in 1976/1978 and 2007/2009, underlining the interest of a multi-disciplinary approach (ergonomics, ergo-toxicology, socio-epidemiology and statistics) that integrated diverse methods for tackling such a complex issue. The goal of the present study was to identify and assess physical and mental demand factors associated with the technical and organizational changes that have occurred since the early 1980s. These results should, on the one hand, support the collective bargaining process concerning retirement age and, more specifically, compensation measures; and, on the other hand, should help to find better technical and organizational arrangements, in particular, prevention measures, likely to reduce the impact of work on the workers’ health. Regarding the short-, middle-, and long-term impact of ergonomic interventions, these studies question the potential of ergonomics to better address issues that are so crucial from an individual as well as social standpoint. They also question whether the body of knowledge produced by ergonomics can be used to steer public policies on occupational health.